Design of La-based MG-Ta composite with high and tailorable properties for solid Ta electrolytic capacitor - Dongjin Chen; Jianan Fu; Shike Huang; Jinbiao Huang; Jian Yang; Shuai Ren; Jiang Ma (Materials & Design, 2024)
Developing a convenient and efficient way of tantalum (Ta) electrolytic capacitor manufacture process is of great importance in many fields, in which a time-saving and energy-efficient tonology of Ta powder consolidation is also desirable. As a typical way to consolidate Ta powder, powder sintering solves the consolidation difficulty of refractory metal like Ta, while the temperature that required are still high which means high energy costs. In the precent work, we tried to apply metallic glass (MG) as a glue to bond the Ta powder at a low temperature (513 k) and successfully obtained the MG-Ta composite due to the excellent thermoplasty of MG. The bonding mechanism between MG and Ta powder was then investigated and the results showed that the MG and Ta were well combined with each other. Moreover, the MG-Ta composite exhibits high performance enhancement with 57 % increased of specific capacitance and 32 % increased of mechanical property than pure Ta. In addition, the specific capacitance of the composite can be improved via acid etching and the mechanism was investigated. Our results provide a facile approach to consolidate the Ta powder with low cost as well as greatly enhance the performance for its application for solid Ta electrolytic capacitor.